ANALISIS FAKTOR-FAKTOR RISIKO INFEKSI KECACINGA MURID SEKOLAH DASAR DI KECAMATAN ANGKOLA TIMUR KABUPATEN Di TAPANULI SELATAN TAHUN 2012 - Juni Fitri; Zulfan Saam; M. Yulis Hamidy (Jurnal Ilmu Lingkungan, 2012)
Basic school students are susceptible to worm infection due to bad personal hygiene andenvironmental sanitary. The risk of infection also related to unsanitary housing in Angkola Timur Regency which population are of low income and low education level. The present study aimed at finding out the prevalency of the worm infection, and the relationship betweenpersonal higiene of student as well as housing sanitary to worm infection. This research isusing descriptive analytic cross sectional design. Purposively 100 individu of the studentfeaces were examined for worm infection in the laboratory. Chi-square analysis wereperformed at confidence level of 95 %., Spearman Rank Corelation were done to evaluate thecorelation of measured variables and logistic regression. It showed that personal hygieneand housing sanitary had significant correlation to infection of worm (Trichiuris trichiura) ofthe students in Angkola Timur Regency. It revealed that the habit of wash hand by thestudents strongly related to the worm infection. It is suggested that the local goverment toimplement the program of the worm infection prevention, in addition to improvement ofcommunity housing sanitation in Angkola Timur Regency. The health extention on clean and healthy habit to basic students as well as student parents, were needed.